Early Childhood Inclusion in Turkey. Issue 3 (July 2016) - Diken, Ibrahim H.; Rakap, Salih; Diken, Ozlem; Tomris, Gozde; Celik, Secil
Abstract : Inclusion of young children with disabilities into regular preschool classrooms is a common practice that has been implemented for several decades in industrialized nations around the world, and many developing countries including Turkey have been developing and implementing laws, regulation, and services to support inclusion and teaching in natural environments. The current definition of inclusion provided in special education laws developed in Turkey aligns with the definition of inclusion provided in the contemporary literature. However, implementation of inclusive practices in early years is still in its early stages and baby steps are taken to develop more comprehensive system of special education and inclusive practices. The purpose of this article is 4-fold: (a) to describe Turkish special education laws and regulations that support inclusive education and teaching in natural environment; (b) to summarize current inclusive practices in early childhood in Turkey; (c) to summarize and synthesize the available research on early childhood inclusion in Turkey; and (d) to discuss challenges and suggestions for future directions to enhance early childhood inclusion in Turkey.